2015
DOI: 10.1080/01402382.2015.1004230
|View full text |Cite
|
Sign up to set email alerts
|

The AfD: Finally a Successful Right-Wing Populist Eurosceptic Party for Germany?

Abstract: Within less than two years of being founded by disgruntled members of the governing CDU, the newly-formed Alternative for Germany (AfD) party has already performed extraordinary well in the 2013 General election, the 2014 EP election, and a string of state elections. Highly unusually by German standards, it campaigned for an end to all efforts to save the Euro and argued for a re-configuration of Germany's foreign policy. This seems to chime with the recent surge in far right voting in Western Europe, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
129
1
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(155 citation statements)
references
References 34 publications
2
129
1
13
Order By: Relevance
“…These observations correspond with the policy proposals and communicative activities of the AfD. The party has explicitly positioned itself as critical of the mainstream media (especially the public broadcasting service; AfD, 2016, p. 48) and operates the most popular German party page on Facebook (see Arzheimer, 2015, for an analysis of its content). 1 Some journalistic analyses pointed to alternative media sources which seem to be popular among AfD sympathizers and which explicitly position themselves outside of or against the political and media mainstream.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…These observations correspond with the policy proposals and communicative activities of the AfD. The party has explicitly positioned itself as critical of the mainstream media (especially the public broadcasting service; AfD, 2016, p. 48) and operates the most popular German party page on Facebook (see Arzheimer, 2015, for an analysis of its content). 1 Some journalistic analyses pointed to alternative media sources which seem to be popular among AfD sympathizers and which explicitly position themselves outside of or against the political and media mainstream.…”
Section: Introductionsupporting
confidence: 62%
“…The comparison of relative source importance within party and user messages indicated that the AfD and its supporters preferred to use somewhat different sources. The party communicators were more likely to refer to more intellectual, conservative-right outlets; the users were more likely to share more controversial and less well-known alternative sources (see also Arzheimer, 2015). This finding suggests that user comments play a substantial part in connecting the AfD-centered information environment on Facebook with more extreme parts of the populist-right online world.…”
Section: Discussionmentioning
confidence: 90%
“…Facebook is the online social network site with the greatest reach in most countries and it is considered an important platform for political communication. Scholars investigated, for example, how political parties communicate on Facebook (Arzheimer, 2015;Magin, Podschuweit, Haßler, & Russmann, 2016;Stier et al, 2018;Stier, Posch, Bleier, & Strohmaier, 2017), how users interact with posts from media organizations' pages (Schmidt et al, 2017), or which (media) sources were referred to by parties and their followers on political pages (Bachl, 2018).…”
Section: An Evaluation Of Retrospective Content Collection On Facebookmentioning
confidence: 99%
“…In an own study, I collected posts, comments, and replies, which were posted on AfD-related Facebook pages during the year 2016, in December 2016 (Bachl, 2018). Arzheimer (2015) was interested in all posts by the party and the users on the main AfD page since its inception in March 2013. The posts were retrieved in July 2014.…”
Section: An Evaluation Of Retrospective Content Collection On Facebookmentioning
confidence: 99%
“…It is argued that the tension between populism and reductionism is characteristic of Western European parties commonly labelled "right-wing populist," which may seek to resolve this tension through a populist logic of partial openings that cuts through the essentialist closure in the equivalential chain so as to enable a selective incorporation of sexual or ethno-linguistic minorities against a common (often "Islamic"; see also Brubaker, 2017) constitutive outside. This is demonstrated in a discourse analysis of the Alternative for Germany (AfD)-a party categorised almost universally as "right-wing populist" in the German political science literature (Franzmann, 2014;Arzheimer, 2015;Bebnowski, 2015;Häusler, 2016;Lewandowsky et al, 2016) -and its development from a "competition populism" (Bebnowski and Förster, 2014;Bebnowski, 2015) into an ethnoculturally reductionist conception of "the people" coexisting with a populist logic of partial openings in relation to LGBT persons and Russian-Germans in the Berlin context in particular.…”
Section: Introductionmentioning
confidence: 99%